Women Decolonising Theologies of, for and by Southeast Asians - Bong, Sharon A. ca. 20./21. Jh. (2022)
The research aim of this project is to offer a critical interrogation of what constitutes the 'Asianness' of doing Christian theology in Southeast Asia. Based on in-depth interviews conducted with six women theologians in the region, and framed within the broader context of the research project that was aimed at decolonising theology, five 'I's may be inductively gleaned: inadequacy, identity, inter-relationality, inclusiveness, and insistence. The paper shows how these Southeast Asian women theologians re-imagine Christianity as an Asian legacy, as a paradigm shift from situating it as a colonial legacy in Asia. By embracing inter-relationality and inclusiveness, they liberate theology in engendering for us, a feministpostcolonial theology of just love and radical hospitality.
Keywords: Christianity; Theologians; Theology